(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Bheramara Upazila of Kushtia District, located in the southwestern part of Bangladesh is one of the most affected areas due to severe water flow reduction in the lower part of the Ganges (the Padma) which is seriously hampering agricultural production. The local people/farmers are tremendously suffering due to water related problems for their domestic as well as agricultural activities. The present study based on the primary field investigation (including open ended questionnaire interview with a total of 100 farmers), key informant interviews and direct field observation attempts to identify farmers perception on water related issues and to understand the process, of how these problems are mitigated both in domestic and agricultural sectors. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15319 J. Asiat. Soc. Bangladesh, Sci. 38(1): 41-52, June 2012